Surgical face masks as a potential source for microplastic pollution in the COVID-19 scenario. (October 2020) - Aragaw, Tadele Assefa
Abstract: Although there have been enormous reports on the microplastic pollution from different plastic products, impacts, controlling mechanisms in recent years, the surgical face masks, made up of polymeric materials, as a source of microplastic pollution potential in the ecosystem are not fully understood and considered yet. Current studies are mostly stated out that microplastics pollution should be a big deal because of their enormous effect on the aquatic biota, and the entire environment. Due to the complicated conditions of the aquatic bodies, microplastics could have multiple effects, and reports so far are still lacking. In addition to real microplastic pollutions which has been known before, face mask as a potential microplastic source could be also researching out, including the management system, in detail. It is noted that face masks are easily ingested by higher organisms, such as fishes, and microorganisms in the aquatic life which will affect the food chain and finally chronic health problems to humans. As a result, microplastic from the face mask should be a focus worldwide. Graphical abstract: Unlabelled Image Highlights: The surgical face mask has been using for the control of Covid-19 pandemics transmissions. The surgical face masks production rates are rising due to fast transmissions of the positive cases. However, the face mask as solid waste macroplastic, and ends up with the microplastic pollutions makes raise environmental threats. The face masks waste management systems attract attention. Microplastic research from the face mask and awareness creation should be a focus worldwide successful to eradicate the problem.